2015
DOI: 10.1556/1646.7.2015.3.7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of aqueous extract of alfalfa on blood glucose and lipids in alloxan-induced diabetic rats

Abstract: Diabetes is a common metabolic disorder that is specifi ed by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. The use of nonpharmacological treatments (herbal agents) is a new approach in the management of diabetes. The aim of this study was to investigate the eff ect of aqueous extract of alfalfa on blood glucose and serum lipids in alloxan-induced diabetic rats. In this study, 32 female rats (210-250 g) were used which were divided randomly into 4 groups including intact c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Insulin deficiency in diabetic patients leads to increased levels of amino acids in the blood, and it will lead to an increase in transaminase activity [ 51 ]. So, the increased level of liver function enzymes; SGPT and SGOT in serum is not only used for the identification of liver damage but also for the metabolic syndrome diabetes mellitus; the liver is one of the organs that is affected by diabetes [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin deficiency in diabetic patients leads to increased levels of amino acids in the blood, and it will lead to an increase in transaminase activity [ 51 ]. So, the increased level of liver function enzymes; SGPT and SGOT in serum is not only used for the identification of liver damage but also for the metabolic syndrome diabetes mellitus; the liver is one of the organs that is affected by diabetes [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…So, the increased level of liver function enzymes; SGPT and SGOT in serum is not only used for the identification of liver damage but also for the metabolic syndrome diabetes mellitus; the liver is one of the organs that is affected by diabetes [ 52 ]. Many studies confirmed that diabetes induction in animals caused tissue lipid peroxidation and hyperlipidemia in many tissues, also caused secretion and release of liver enzymes to circulation [ 51 ]. The current results showed that oral administration of PA flower ethanolic extracts for 15 days induced a significant decrease in the activity of these enzymes in diabetic rats, suggesting that PA has a hepato-protective effect and ameliorates alteration in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoglycemic effect of alfalfa leave and its constituents had been proven in the screening study. Since alfalfa stimulates insulin secretion, the pancreatic islet is a possible target of alfalfa (Amraie et al, 2015). Aqueous extract of alfalfa leaves (1 gm/ml) increased insulin secretion from the BRIN-BD11 pancreatic β-cell line (Pancreatic islets from rat) at 16.7 mmol glucose concentration.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, identification of new approaches such as the use of specific food components may provide potential prevention and management of Type II diabetes. Alfalfa or green gold is one of the medicinal plants that are used in traditional medicine due to being high in protein, calcium, and vitamins and also its low percentage of cellulose (Amraie et al, 2015). Leaves of alfalfa have been used traditionally in South Africa for treating diabetes in the form of tea (Gray and Flatt, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, numerous scientific investigations have led to the confirmation of therapeutic value of medicinal plants. Medicago Sativa used to be known/named as the Queen of Plants and Green Gold (12). The plant is rich in various proteins, calcium, mineral elements, various vitamins in group B, vitamins A, C, D, E, K and amylase enzyme, emulcer, invertase and pectinase, as well as very small amounts of arsenic and silica (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%